ANALISIS MANAJEMEN SYARIAH TERHADAP KEBIJAKAN PIZZA HUT DELIVERY DALAM PENANGANAN SUMBER DAYA MANUSIA DI MASA PANDEMI COVID-19 (STUDI PADA PIZZA HUT DELIVERY LEUWILIANG KABUPATEN BOGOR) - M. Parid Dudin; Tubagus Rifqy Thantawi; Susi Melinasari (SAHID BUSINESS JOURNAL, 2022)
The Covid-19 pandemic has affected restaurateurs so that the company has used various methods to boost sales, including a pick-up strategy to create roadside booths such as what Pizza Hut Delivery has done, including at its branches such as Pizza Hut Delivery Leuwiliang, Bogor Regency. This also affects human resource policies, so that human resource management is adapted to the circumstances of the Covid-19 pandemic. Even so, the situation was quite severe during the Covid-19 pandemic, Pizza Hut Delivery's policy in handling human resources during the Covid-19 pandemic was to pay attention to the rights and obligations of employees in terms of human resource policies such as health policies, working hours policies, honorarium salary and allowance policies, bonus policies, transfer and promotion policies, and employment termination policies. Human resource policies during the Covid-19 pandemic are still based on laws and regulations issued by the central and regional governments. In addition, by paying attention to the work agreement. This makes the sharia management analysis of the Pizza Hut Delivery policy quite balanced by taking into account the interests of the company and the interests of its employees or human resources.